O trabalho do profissional de psicologia na atuação em cuidados paliativos: uma análise da morte e do morrer - Amaral, Jacqueline Andrade (2023)
The following study addresses the work of psychologists in Palliative Care, who experience, alongside both patients and relatives, moments of finitude in situations that have death as one of the possible outcomes. The COVID-19 pandemic highlighted psychologists’ roles within multiprofessional teams which were based on a transdisciplinary approach. However, it is noted that the theories and competences which handle death and the process of dying are yet to be included in the national curricular directives of Psychology university programs, which leads to questioning whether Psychology professionals are actually well-prepared to work in the aforementioned field. This research focuses on the work of psychologists who handle death and the process of dying within Palliative Care teams. To reach the objective established, the experiences of psychologists in multiprofissional palliative care teams, when working with patients and relatives, were taken into account, emphasizing the competences and abilities required for interventions in situations which include death and the process of dying. The methodological course was of qualitative research, using narrative interviews as the method of choice. This allowed the apprehension of significant and subjective data regarding historical and sociocultural aspects, which provided a privileged space for speech and elaboration of life stories. In this study, three persons were interviewed, all three having worked in the Palliative Care field for at least two years. Results confirmed that psychologists’ knowledge regarding death and the process of dying is scarce, and that, to work in the palliative care field, Psychology professionals require theoretical knowledge. Considering said results, the present research indicates a need for inclusion of death and the process of dying in Psychology university programs, which might contribute to forming a holistic view of humanity.